Pengembangan Pola Bisnis Rintisan (Start-up) Mahasiswa Wirausaha Universitas Andalas - Tivany Edwin; Berri Brilliant Albar; Uyung Gatot Syafrawi Dinata (Warta Pengabdian Andalas, 2021)
The unemployment rate is high, even among university graduates, due to the lack of expertise required for work. Andalas University is one of the universities that support student entrepreneurship. One of the efforts made is the existence of compulsory Entrepreneurship courses for all registered students. Entrepreneurship activities are one of the Independent Learning Campus (MBKM) programs intending to respond to the challenges of graduates becoming qualified human resources. They can create employment opportunities and be entrepreneurial experienced. This community engagement activity was essential, with the target community being entrepreneurial students starting startups in 2020. Students were developing twenty-four startup businesses. The food beverage sector, including cultivation, is essential—other running businesses, in addition to the clothing or fashion, handicraft, pharmaceutical, beauty and service businesses. The team formulated the stages of business development for the startup pattern starting from the completeness of business legality to the technical scale-up of the business. Entrepreneurial students must have assistance from Andalas University lecturers, who can cooperate with the companies, enriching the student's business experience before entering the post-campus period.